HUBUNGAN KONSUMSI KOPI DAN STATUS MEROKOK DENGAN KEJADIAN HIPERTENSI DI DESA KRUENG BATU KECAMATAN KLUET UATARA KABUPATEN ACEH SELATAN - Nursani Nursani; Cukri Rahma; Itza Mulyani; Teuku Muliadi (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2026)
The title of this research is "The Relationship Between Coffee Consumption and Smoking and the Incidence of Hypertension in the Elderly in Krueng Batu Village, Kluet Utara District, South Aceh Regency," and its goal is to clarify the connection between the two variables and the increased hypertension risk in the elderly.   A cross-sectional design was used in the study with 84 participants.   The results demonstrated a connection between smoking and hypertension (? = 0.005) and a strong association between coffee consumption and hypertension (? = 0.0012).   When it comes to hypertension in the elderly, it's best to spread more information, limit coffee use, and not smoke.   In order to lower the likelihood of long-term difficulties, community members may utilize the study's results to influence their own healthy eating habits.